Barriers to affordable housing on brownfield sites. (March 2021) - Squires, Graham; Hutchison, Norman
Highlights: An investigation in overcoming the economic and financial barriers that prevent affordable housing on brownfield sites. The case studies cover the development of three large scale brownfield sites that integrate affordable housing in the City of San Francisco. Theoretical barriers include: (1) economic geography; and (2) economic viability and sustainability. More practical barriers include: (3) affordable housing quality; and (4) transcending scale for policy efficacy. Discussion that viability includes internal-external costs of quality when building affordable housing on large-scale brownfield land. Abstract: Brownfield development incorporates both private and public costs due to the contamination of land. Furthermore, brownfield sites generate negative externalities on real estate viability, and are perceived to be risky and costly for development. Viability risk makes affordable housing development on brownfield sites even more financially and economically challenging. To understand this issue, this paper introduces a conceptual model to analyse and overcome the economic and financial barriers to meet both community and environmental concerns, as well as verifying how it holds in practice via case studies that cover the development of three large scale brownfield sites that integrate affordable housing in the City of San Francisco. Significant barriers to overcome include (1) engaging with economic geography rationale; (2) integrating with economic viability and sustainability concerns; (3) increasing affordable housing quality; and (4) transcending scale to improve policy tool efficacy. Conclusions argue that viability needs to consider cost-quality both internally and externally for high-quality affordable housing units in large-scale brownfield environments.